Effect of ph changes on the growth of selected bacteria in coconut milk - Marahaini, Musa (Universiti Sains Malaysia, 2009)
Coconuts (Cocos nucifera) are found growing around the world in lowland, tropical and subtropical habitats and have been used as a valuable source not only for food but also as medicine. One of the coconut's product used as medicine is coconut milk. Coconut milk is the aqueous extract of the solid coconut endosperm. It is a low-acid liquid food, with a pH of around 6.2 and very rich in nutrient. These properties of coconut milk provides suitable medium for growth of microorganisms. Effective methods of sterilization are practiced to eliminate hannful microorganism, making coconut milk safe to be consumed. A preservation technique used in general food preservation is by the addition of chemicals. These chemicals include acids and bases which alter pH of food and inhibit growth of certain bacteria. In this research, we study effect of pH changes on selective bacteria growing in coconut milk. Coconut milk samples are subjected to different pH ranging from acidic to alkaline, started from pH 1 0, 8, 6, 4 and 2. Control sample is prepared without addition of chemicals. Sample is inoculated on MacConkey and MRS agar in order to identify selective bacteria growing in coconut milk. Morphology of bacteria is examined under microscope and biochemical tests are conducted for identification of bacteria. pH reductions are recorded throughout the experiment except for pH 2 group. Bacteria count (CFU/ml) is recorded over time. We found that pH changes affect the growth rate of bacteria in coconut. Klebsiella pnemoniae, Acenitobacter and Staphylococcus prefer alkaline condition whereas Lactobacillus grows better at acidic pH. Gathered information could provide clearer guidance towards activities which need information about bacterial growth, for example in development of new media for growth of selected bacteria.